(untitled) - Pruitt, Nancy L. (New York, 2003)
Learning about living things is like piecing together a complex puzzle. BioInquiry: Making Connections in Biology, a National Science Foundation-supported project (DUE #97-52454), was designed to help you assemble these pieces, to see their connections, and to reveal the beautiful and compelling pictures they create. The text, CD, and web site were developed together from the start to create an engaging, active learning experience. You’ll take a virtual tour of the cell, travel with Darwin to the Galápagos Islands, transcribe DNA, perform powerful experiments, and link to the latest biological research on web sites around the world. You’ll experience for yourself the profound biological discoveries that forever changed the way we think about life. Enjoy your explorations! --This text refers to an out of print or unavailable edition of this title.
Keywords: Biology